Functions of the criminal investigation authority in Saudi partial Criminal procedure System - Mohammed, Yasmeen Ahmad (Journal of Economic, Administrative and Legal Sciences, 2023)
The criminal investigation authority is the authority competent to collect information and evidence necessary for the investigation and to file an accusation as the preliminary stage for filing a criminal case before the judicial authorities The task of the criminal investigation officer begins after the actual occurrence of the crime, that is, it begins when the administrative control authority (whose task is to prevent the crime, such as the civil defense, the Coast Guard, etc...) is unable to prevent the crime. The criminal investigation officer may initiate any procedure that is necessary to reach the truth provided that he observes the procedural legitimacy. This system guarantees individual freedom and procedural legality. No person is arrested, arrested, searched, or his home searched except in the cases stipulated in the law, and it is prohibited to subject him to torture or physical or moral coercion.